The Role of Talent Development in Organizational Change: A Bibliometric Analysis of Global Corporate Trends - Judijanto, Loso; Apriyanto, Apriyanto; Maria, Siti; Purwinahyu, Purwinahyu; Aini, Rohana Nur (Westscience Press, 2024)
The evolution and key themes in the field of talent management research from 2000 to 2024 are highlighted in this study's thorough bibliometric analysis and thematic overview. Effective human resource strategies inside organizations are determined to be based on the fundamental elements of talent management, which include leadership, training and development, and organizational performance. It is acknowledged that the incorporation of technology innovations, including big data, machine learning, and digital transformation, has a revolutionary impact on talent management procedures by permitting more predictive and data-driven methods. In addition to discussing the implications of diversity and inclusion in cultivating a creative and flexible workforce, this study examines the strategic significance of matching organizational objectives with talent management in order to improve competitive advantage. The study also discusses the potential and problems associated with technology integration in human resources, stressing the importance of ethical concerns and upholding a human-centered approach in the face of technological breakthroughs.